Historiographie de l’américanisme scientifique français au xixe siècle : le « prix Palenque » (1826-1839) ou le choix archæologique de Jomard - Nadia Prévost Urkidi (Journal de la Société des Américanistes)
Historiography of the French scientific Americanism in the 19th century: the « Palenque prize » (1826-1839) or the archaeological choice of Jomard. For Carlos Navarrete, the « discovery » of the ruins of Palenque was « the beginning of the Mayan archaeological adventure ». The impact of this discovery went beyond this Mayan archaeological field thanks to the prize about the « American Antiquities » which the Société de Géographie de Paris proposed between 1826 and 1839. During thirteen years, this competition, which had for main object the study of the ruins of Palenque and its neighbourhoods, indeed created a general dynamic not only in France but also on an international plan around what the Parisian learned world still called the « American studies ». About this prize however, nobody knows really much. The analysis of the Bulletins de la Société de Géographie de Paris allows nevertheless to reconstruct the framework of the « Palenque prize » and to determine the theoretical and methodological impact for the nascent scientific americanism.